THE PROFILE OF CORONARY HEART DISEASE PATIENTS IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Ogiska Chaherfa Nadasya; Johanes Nugroho Eko Putranto; I Ketut Sudiana; Agus Subagjo (Majalah Biomorfologi, 2021)
Background: Coronary heart disease is a deadly disease for human. The incidence of coronary heart disease is different, so that this research reported the profile of coronary heart disease patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Objective: To analyze the profile of CHD patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia from February to September 2018. Materials and Methods: A descriptive research based on the medical records. Results: There were 65 male patients and 20 female patients. There were 58% patients aged 50-60 years old, 24% patients aged more than 60 years old, and 18% patients are under 50 years old. The patients’ occupations were as follows: 42% civil servants, 36% private employees, 9% housewives, 5% retirees, 3% entrepreneurs, 1% for teacher, driver, fisherman, priest, and merchant. The complaints included chest pain (40%), shortness of breath (23.5%), PCI (4.6%), thump chest (1.2%), lower right abdominal pain (1.2%), right leg pain (1.2%), nausea (1.2%), vomitting (1.2%), cough (1.2%), dysentry (1.2%), and no complaint (23.5%). CHD patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia had the history of hypertension (30.6%), heart disease (22.6%), diabetes mellitus (21.9%), smoking (5.6%), COPD (0.8%), and no history of disease (12.9%). Sixty-one percent of the patients had blood sugar level of  ≥100 mg/dl, 19% patients had blood sugar level of <100 mg/dl, 20% patients did not have data. Conclusion: There were 85 patients, predominantly males of 50-60 years old. The most common occupation of the patients was civil servant and they came with major complaint of chest pain with the history of hypertension.